Regional variation in firm formation: Panel and cross-sectional data evidence from Finland - Aki Kangasharju (European Regional Science Association (ERSA), 1998)
This paper investigates regional variation in firm formation in Finland between 1989 and 1993. Firstly, the paper describes the firm formation process in 19 regions and 88 subregions, and finds that there has been a clear variation in firm formation across those areas. Secondly, the paper discusses the regional factors which in the literature have most often been found to affect firm formation at the regional level, and estimates the effects of those factors on firm formation utilizing panel data which consists of the Finnish subregions and the five years from 1989 to 1993. Panel data evidence show that the presence of small firms tends most robustly to explain firm formation in Finland. Thirdly, the paper estimates the effects of those regional factors on firm foundation in Finland using cross-sectional data, and compares the results with those obtained by similar methods for several European countries and the USA. Cross-sectional results tend to show that demand growth is also an important factor explaining regional firm formation. An additional finding is that cross- sectional results for Finland appear to be similar to those for other countries, whereas panel data results tend to be somewhat poorer. This implies that there is substantial variation in entry conditions across subregions, and that some of the effects of these entry conditions are being captured by subregion-specific intercept terms, rather than by the explanatory variables used.
Keywords: 330